SAT0473 MUSCULOSKELETAL STIFFNESS IN CHIKUNGUNYA DISEASE: DISTINCT FROM PAIN AND RELEVANT TO QUALITY OF LIFE. (June 2019) - Watson, Hugh; Tritsch, Sarah; Encinales, Liliana; Cadena, Andres; Cure, Carlos; Porras, Alexandra; Mendoza, Alejandro Rico; Chang, Aileen
Abstract : Background: Musculoskeletal stiffness is reported to be frequent following chikungunya infection and can persist for many months after infection. However, stiffness severity and its impact is not well characterised in this disease. A stiffness patient reported outcome instrument has been developed for use in rheumatoid arthritis. Objectives: Our objective was to assess the use of this questionnaire and importance of musculoskeletal stiffness in a cohort of chikungunya patients with chronic joint symptoms in the Atlántico Department of Colombia. Methods: Sixty-seven patients with chronic arthralgia and 15 patients without arthralgia were followed up a mean of 40 months after chikungunya infection. The patients came from a larger cohort of 500 patients previously followed up 20 months after infection. Those consenting to a 40-month in-person follow-up were included here. Tender joint counts, a pain intensity visual analogue scale (VAS), Health Assessment Questionnaire-Disability Index (HAQ-DI) and the EuroQol overall health VAS (EQ-VAS) were completed. A 21-item musculoskeletal stiffness questionnaire (MSQ) was completed and summarized as percentage scores for overall stiffness and its components: stiffness severity, physical impact and psychosocial impact. Results: The 82 patients (12 male and 70 female) had a mean age 51±14 years. Forty-two out of sixty-seven patients with arthralgia and 3/15 patients without arthralgia reported musculoskeletal stiffness. Stiffness in those patients had a median severity of 28% (IQR 0-42). An impact of their stiffness on physical activities was reported by 39/45 patients (87%) and psychosocial impact by 32/45 patients (71%). Overall MSQ score was a median of 16% (IQR 0-34). Mean tender joint count in patients reporting arthralgia was 6.2±7.1, mean pain intensity 65±20 out of 100, mean HAQ-DI = 0.54±0.52, and a mean EQ-VAS = 68±62 out of 100. Overall stiffness scores were poorly correlated with tender joint counts (r 2 =0.17) and pain intensity (r 2 =0.22). Stiffness scores were more strongly associated with the HAQ-DI (r 2 =0.52) and EQ-VAS overall health VAS scores (r 2 =0.46), whereas tender joint counts were not: r 2 =0.22 for HAQ-DI and r 2 =0.21 for EQ-VAS. Conclusion: Musculoskeletal stiffness following chikungunya infection is distinct from the persistent arthralgia usually reported. It does not necessarily occur in the same patients and is poorly correlated with joint pain severity. Stiffness, as measured by this questionnaire, may be more strongly associated than arthralgia with overall health and disability indices in patients with chikungunya disease. The MSQ is a potentially useful instrument for assessing symptoms in chronic chikungunya disease. Disclosure of Interests: Hugh Watson Shareholder of: Sanofi, Employee of: Sanofi, Sarah Tritsch: None declared, Liliana Encinales: None declared, Andres Cadena: None declared, Carlos Cure: None declared, Alexandra Porras: None declared, Alejandro Rico Mendoza: None declared, Aileen Chang: None declared